Análise da sustentabilidade da produção de carvão vegetal na Paraíba - Pinheiro, Lídio Lima (2012)
This dissertation examined the sustainability of the production of charcoal from a company in the state of Paraiba, using for that, the tool DASHBOARD OF SUSTAINABILITY. The company is a charcoal legalized whose headquarters is located in the state capital, João Pessoa, and its operating plant is located in the municipality of Emas, the region known as Seridó Paraiba. The charcoal has a unique differential is that I form your denominated Darkening Semi-Solid Metal. It is produced and a furnace created by the client company production capacity compared to conventional furnace becomes seven times faster, having a mean production of carbon 24 hours (1 day) medium against seven days coal production in the other. To achieve this work we decided to use the criteria established in 2010 by FAO through its document entitled Criteria and Indicators for Sustainable Woodfuels. The measurement of markers was performed using a comparative method, this method used by the tool adopted, which established itself as the perfect setting when the same is not indicated by the index or indicator, compliance with standards set by internationally recognized institutions, as the UN, ILO and WHO making a counter-point with respect to the situation found in the research, thus obtaining a result. In the search results is shown in the analysis dimensions: economic, social, institutional and environmental aspects of coal bunker, and his own, after consideration of the four dimensions analyzed, obtained a satisfactory level of sustainability according to the DASHBOARD.